Rapid genomic first- and second-line drug resistance prediction from clinical Mycobacterium tuberculosis specimens using Deeplex-MycTB. Issue 1 (5th January 2021) - Feuerriegel, Silke; Kohl, Thomas A.; Utpatel, Christian; Andres, Sönke; Maurer, Florian P.; Heyckendorf, Jan; Jouet, Agathe; Badalato, Nelly; Foray, Lynda; Fouad Kamara, Rashidatu; Conteh, Osman S.; Supply, Philip; et al.
The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis complex (Mtbc) isolates challenges tuberculosis (TB) control worldwide [1] and requires the rapid determination of extensive resistance profiles [2], enabling prompt initiation of effective treatment regimens. Phenotypic drug susceptibility testing (pDST) takes up to 6 weeks [3], and is unreliable and/or not standardised for several drugs, according to World Health Organization (WHO) guidelines [4]. Molecular DST (mDST) assays, like Xpert MTB/RIF (Cepheid) or MTBDR plus / sl line probe assays (LPAs; Hain Lifesciences) can be performed directly from clinical specimens, but only target a limited number of resistance variants [5]. Targeted next generation sequencing using the Deeplex-MycTB assay can rapidly generate comprehensive drug resistance profiles from Mycobacterium tuberculosis complex cultures and directly from tuberculosis patient samples to guide personalised treatment https://bit.ly/3dP1eIp